2016
DOI: 10.1089/acm.2015.0351
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Executive Attention, Rumination, Cognitive Reactivity, and Mindfulness Among High–Suicide Risk Patients Participating in Adjunct Mindfulness-Based Cognitive Therapy: Preliminary Findings

Abstract: Findings from the present pilot study suggest that treatment with MBCT-S may improve cognitive deficits specific to suicide ideators and attempters among depressed patients. Future controlled trials using follow-up assessments are needed to determine the specificity of these improvements in cognitive functioning to MBCT-S and their durability and to formally test whether the observed improvements in cognitive functioning explain MBCT-S treatment gains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(27 citation statements)
references
References 47 publications
3
22
0
Order By: Relevance
“…There is some evidence that the mitigation of certain cognitive processes is important for reducing the psychopathology associated with SI. One study found that high‐risk suicidal individuals showed improvements in executive attention and mindfulness and decreases in rumination and cognitive reactivity after receiving a short, mindfulness‐based cognitive therapy (Chesin et al, ). In addition, mindfulness has been shown to be positively correlated with attention and concentration (e.g., Jha, Krompinger, & Baime, ) and has been shown to be related to decreases in attentional biases (e.g., Garland, Boettiger, Gaylord, Chanon, & Howard, ).…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that the mitigation of certain cognitive processes is important for reducing the psychopathology associated with SI. One study found that high‐risk suicidal individuals showed improvements in executive attention and mindfulness and decreases in rumination and cognitive reactivity after receiving a short, mindfulness‐based cognitive therapy (Chesin et al, ). In addition, mindfulness has been shown to be positively correlated with attention and concentration (e.g., Jha, Krompinger, & Baime, ) and has been shown to be related to decreases in attentional biases (e.g., Garland, Boettiger, Gaylord, Chanon, & Howard, ).…”
Section: Discussionmentioning
confidence: 99%
“…Executive function at baseline has been found to predict response to treatment for depression (Dawson et al., ). Mindfulness based cognitive therapy combined with safety planning delivered over 9 weeks improved cognitive functioning in a suicidal depressed sample, but was not associated with a decrease in suicidal ideation (Chesin et al., ). The assessment of neurocognitive correlates associated with depression may provide an avenue for future research to guide the development of interventions (Sommerfeldt et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…This contributes to decrease experiential avoidance from unpleasant psychological events (as they are simply considered as harmless attentional objects), contributing to decrease suicidal thoughts and acts . Interestingly, it has been shown that training in mindfulness weakens the association between depressive symptoms and suicidal ideation in depressed patients , through decrease in cognitive reactivity and ruminations . Besides, trait mindfulness has been negatively correlated to lability of negative affects, independently of depression and mediated by lower maladaptive coping.…”
Section: Discussionmentioning
confidence: 99%